Identifying Diagnostic Genetic Markers for a Cryptic Invasive Agricultural Pest: A Test Case Using the Apple Maggot Fly (Diptera: Tephritidae). (16th March 2020) - Doellman, Meredith M; Hood, Glen R; Gersfeld, Jacob; Driscoe, Amanda; Xu, Charles C Y; Sheehy, Ryan N; Holmes, Noah; Yee, Wee L; Feder, Jeffrey L
Abstract: Insect pests destroy 15% of all U.S. crops, resulting in losses of 15 billion annually. Thus, developing cheap, quick, and reliable methods for detecting harmful species is critical to curtail insect damage and lessen economic impact. The apple maggot fly, Rhagoletis pomonella, is a major invasive pest threatening the multibillion-dollar apple industry in the Pacific Northwest United States. The fly is also sympatric with a benign but morphologically similar and genetically closely related species, R. zephyria, which attacks noncommercial snowberry. Unambiguous species identification is essential due to a zero-infestation policy of apple maggot for fruit export. Mistaking R. zephyria for R. pomonella triggers unnecessary and costly quarantines, diverting valuable control resources. Here we develop and apply a relatively simple and cost-effective diagnostic approach using Illumina sequencing of double-digest restriction site-associated DNA markers. We identified five informative single-nucleotide polymorphisms (SNPs) and designed a diagnostic test based on agarose gel electrophoresis of restriction enzyme-digested polymerase chain reaction amplification products (RFLPs) to distinguish fly species. We demonstrated the utility of this approach for immediate, 1-d species identification by scoring apple- and snowberry-infesting flies from known hosts, reared from fruit collected at 11 sites throughout Washington. However, if immediate diagnosis is not required, or hundreds to thousands of specimens must be assessed, then a direct Illumina-based sequencing strategy, similar to that used here for diagnostic SNP identification, can be powerful and cost-effective. The genomic strategy we present is effective for R. pomonella and also transferable to many cryptic pests.